The human microbiome in clinical translation: from bench to bedside - Bautista, Jhommara; Echeverría, Carolina E.; Maldonado-Noboa, Iván; Ojeda-Mosquera, Sofía; Hidalgo-Tinoco, Camila; López-Cortés, Andrés (Frontiers in Microbiology, 2025)
The human microbiome, once regarded as a passive passenger, is now recognized as a dynamic and essential determinant of human physiology, shaping immunity, metabolism, neurodevelopment, and therapeutic responsiveness across the lifespan. Advances in multi-omic technologies, experimental models, and computational approaches have revealed mechanistic insights into how microbial communities modulate host systems across diverse body sites, including the gut, skin, lungs, oral cavity, and reproductive tract. The clinical translation of this knowledge has begun to redefine early-life programming, cardiometabolic regulation, immune homeostasis, neuropsychiatric resilience, and cancer therapy response. Innovative strategies such as phage therapy, live biotherapeutics, precision nutrition, and microbiota transplantation illustrate the therapeutic potential of harnessing microbial functions to prevent or treat disease. In parallel, large-scale initiatives cataloging the microbiome of underexplored niches, such as the vagina and skin, are advancing health equity by broadening representation in microbial reference datasets. Yet significant challenges persist, including interindividual variability, incomplete functional annotation of microbial “dark matter,” and the absence of validated biomarkers. Addressing these gaps requires standardized methodologies, harmonized regulatory frameworks, and longitudinal studies across diverse populations. This review outlines the progress and remaining hurdles in translating microbiome science into clinical practice and concludes that the microbiome now stands at the forefront of a paradigm shift, transforming concepts of disease etiology, therapeutic design, and the future of individualized medicine.